RELIGIOUS EXPANSION OF TURKEY IN TATARSTAN IN THE POST-SOVIET PERIOD - R. R. Suleymanov (Vestnik MGIMO-Universiteta)
Turkey considers Tatarstan a sphere of its geopolitical interests in the framework of pan-Turkism concepts. With the collapse of the USSR Ankara began to pursue an active policy in the Volga region, strengthening its influence there. One of the Turkish policies towards Tatarstan became religious expansion. Islamic Jamaat of Turkey sent its missionaries to Tatarstan. This led to the fact that some Muslims of Tatarstan began to focus on Turkey and the spiritually obey Turkish sheikhs. Authorities in Tatarstan treated religious intervention of Turkey in the region favorably. The ideological rapprochement with Turkey was a part of the foreign policy strategy of Tatarstan elite that after gaining independence in the early 1990s saw in Ankara a natural ally. Turkey acted as a "big brother" for Tatarstan. The religious sphere of cooperation was seen as one of the factors bringing the two Turkic republics togather. A huge variety of Turkish islamic jamaats in Tatarstan is due to the fact that Ankara has actively supported the religious expansion in those regions that are a zone of its interests. And often those religious groups that were in opposition to the Turkish authorities inside Turkey, are supported by Ankara outside the country in their missionary work.